The Key role of MRI modalities in En Plaque Meningioma - Tirtaprawita, Novita; Wiradharma, Wiradharma; July, Julius (Fakultas Kedokteran Universitas Pelita Harapan, 2017)
En plaque meningioma is at frontal region is difficult to be differentiated from osteoma, based on CT scan only. En plaque meningioma represents in 2-9% of all meningioma cases. Usually en plaque meningioma grows on the sphenoid wing, whereas only 1 % grows on the frontal and temporal bone. This case is female 37 year- old who presents with chronic headache and huge lump on her right forehead that she believes it slowly enlarges for the last 5 years. The Computerized Tomography scan (CT scan) shows thickening of the right fronto-temporal bone (3-4 cm) with the diameter of 12 cm and bony hard. Initial impression suggests it could be osteoma or fibrous dysplasia. After the MRI (Magnetic Resonance Imaging) with contrast, it shows a carpet like tumor underline the thickening bone, and it suggest an en plaque meningioma. For en plaque meningioma, we have to remove the abnormal duramater. We suggest that for a case with a wide thickening calvarian bone, it’s better to get the MRI of the head with contrast.